Knowledge, Attitude, and Practice Toward Cardiovascular Diseases in the Lebanese Population - Marc Machaalani; Battoul Fakhry; Maisoon Zwaihed; Karl Mendelek; Nadine Mahmoud; Talal Hammoud; Mirna N. Chahine (Ubiquity Press, 2022)
Background & Objective: Cardiovascular diseases (CVD) are the leading cause of death globally. Assessing CVD knowledge, attitude, and practice (KAP) is necessary to spread awareness about CVD in Lebanon, their corresponding risk factors, and behaviors in which individuals can avoid or minimize the possibility of developing a CVD. Subjects & Methods: This was a case-control analytical study that targeted 921 CVD and non-CVD subjects. A questionnaire form was used to collect data related to patients' demographics, socioeconomic status, habits, medical and family history, KAP towards CVD, and source of information. Data was analyzed using SPSS v.25. Results: Data from 921 participants were distributed over the CVD group (52.6% males aged 58.3 ± 13.7 years [n = 460]) and the non-CVD group (47.7% males aged 36.3 ± 15.4 years [n = 461]). CVD patients were significantly older than non-CVD subjects (p < 0.001). All three KAP scores of both groups were of poor to fair levels. Both CVD knowledge and attitude mean scores in CVD patients (26.6 ± 5.2 over 40 [66.50%] and 63.3 ± 10.2 over 85 [74.47%], respectively) were significantly higher than the ones of non-CVD subjects (23.5 ± 7.9 over 40 [58.75%] and 61.4 ± 12.4 over 85 [72.74%], respectively, p < 0.001). However, the CVD mean practice score was significantly lower in CVD patients (6.0 ± 1.7 over 9 [66.67%]) than the one of non-CVD subjects (6.3 ± 2.2 over 9 [70.00%] p < 0.001). Mostly, educational level (p < 0.001), governorate (p < 0.01), and smoking (p < 0.001) were predictors of KAP CVD in both groups. Conclusion: With an overall limited knowledge, attitude, and practice toward CVDs, the Lebanese population (with CVD or non-CVD) needs targeted national campaigns about CVD according to the identified predictors of CVD KAP to prevent and to alleviate the complications due to CVDs.